2017
DOI: 10.1016/j.ijscr.2017.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous V 2 of the left pulmonary vein detected using three-dimensional computed tomography in a patient with lung cancer: A case report

Abstract: HighlightsWe report the rare anatomical variations of the pulmonary vein wherein the left V2 drained into the inferior pulmonary vein.The left V2 draining into the inferior pulmonary vein has not been yet reported, and this case is the first report.We identify this anomalous V2 before operation by 3D-CT and were able to perform the operation safely by VATS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In the report about variations of the course of the PV by Shiina et al, the prevalence on the left side was 2.6%, which was less frequent than on the right side at 32.8% [16]. Among variations of the course of left V 1+2 , the variation that passed to the dorsal side of the pulmonary hilum and joined V 6 or the inferior PV was more frequent than the others [17, 18]. In the present case, the left V 1+2 passed between B 6 and the bronchus to the basal segment and joined V 6 at the dorsal side of the pulmonary hilum.…”
Section: Discussionmentioning
confidence: 99%
“…In the report about variations of the course of the PV by Shiina et al, the prevalence on the left side was 2.6%, which was less frequent than on the right side at 32.8% [16]. Among variations of the course of left V 1+2 , the variation that passed to the dorsal side of the pulmonary hilum and joined V 6 or the inferior PV was more frequent than the others [17, 18]. In the present case, the left V 1+2 passed between B 6 and the bronchus to the basal segment and joined V 6 at the dorsal side of the pulmonary hilum.…”
Section: Discussionmentioning
confidence: 99%
“…5 On the left side, the most prevalent variation found in humans is the common trunk of the left superior and inferior pulmonary vein but various unusual patterns have been observed as venous branches from the lingular segment (V 4 þ V 5 ) emptying into the inferior pulmonary vein; inferior lingular pulmonary vein (V 5 ) draining into the left atrium; anomalous vein for the apicoposterior segment of the left upper lobe (V 2 ) draining into the left inferior pulmonary vein; and lower lobe apical segmental vein (V 6 ) flow in the superior pulmonary vein. 2,6,7 Usually, right-sided variations are more frequent than on the left side. Some authors have reported middle lobe veins joining the inferior pulmonary vein as a single trunk or separately, independent drainage of the middle lobe veins directly into the left atrium or the lateral part of the middle lobe vein (V 4 ) and the medial part of the middle lobe vein (V 5 ) draining, respectively, into the inferior and superior pulmonary vein.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative CT scan identification of anatomical variations in the pulmonary venous system may help prevent iatrogenic complications such as uncontrolled bleeding, severe lung edema, or extension of pulmonary resections. 7 Pulmonary vascular anomalies sometimes are not detected on preoperative CT scans and for this reason we always recommend a careful dissection during major lung resections, especially in minimally invasive thoracic surgery where homeostasis following vessel injury can be more complicated. 2…”
Section: Discussionmentioning
confidence: 99%
“…Aragaki et al . reported preoperative recognition of the left V 2 draining into V 6 on 3D‐CT and the successful preservation of the V 5 during VATS LLL resection . Ishikawa et al .…”
Section: Discussionmentioning
confidence: 99%